Taxonomic and Functional Dynamics of Bacterial Communities During Drift Seaweed Vermicomposting - Manuel Aira; Ana Gómez-Roel; Jorge Domínguez (Microorganisms)
Seaweed is a valuable natural resource, but drift or beach-cast seaweed is considered a waste product. Although seaweed is traditionally used as an organic amendment, vermicomposting has the potential to transform the material into valuable organic fertilizer, thereby enhancing its microbial properties. This study aimed to investigate the dynamics of the taxonomic and functional bacterial communities in seaweed during the vermicomposting process by high-throughput sequencing of 16S rRNA gene amplicons. Vermicomposting changed the composition of the bacterial communities, as indicated by the low proportion of bacterial taxa common to the bacterial communities in the raw seaweed and vermicompost (21 to 56 ASVs from more than 900 ASVs per sample type). The observed increase in taxonomic diversity (32% mean increase across sampling times) also affected the functionality of the bacterial communities present in the vermicompost. The diverse bacterial community showed enriched functional pathways related to soil health and plant growth, including the synthesis of antibiotics, amino acids, and phytohormones, as well as the degradation of bisphenol. In conclusion, in terms of microbial load and diversity, vermicompost derived from seaweed is a more valuable organic fertiliser than seaweed itself.